Investigation of thermal similarity and performances of solar thermal air collector with heat-soaked vehicle cabin - Lahimer, Adel Abulgasm; Amir, Abdul Razak; Kamaruzzaman, Sopian (Semarak Ilmu Publishing, 2024)
This article explores the potential of vehicle interiors, which can reach temperatures of up to 120°C due to solar exposure, as efficient solar collectors. Comparative studies have been conducted on the thermal behavior of heat-soaked vehicle cabins and dedicated solar collectors, highlighting their potential benefits in heating, cooling and ventilation. Thermal soak tests reveal a remarkable similarity in thermal performance between the two, with minor temperature variations of up to 5.3°C between the equivalent components. These temperature deviations are mainly due to differences in absorptivity characteristics, in which the black absorber plate exhibits superior absorption capabilities compared to the grey interior cabin surfaces. Integration of ambient air through the inlets on the cabin floor helps with initial cooling of the hot soaked cabin. The collector benefits from a preheated air mixture (comprising heat-soaked cabin air and ambient air), which improves its operating temperatures. This characteristic is attributed to the synergistic integration of the two systems. By decoupling these systems and aligning the properties of the absorber plate, the cabin and the collector could become thermally identical. The potential of the heated vehicle cabin as a power generation source is underscored, which presents opportunities to supplement the energy demand in remote locations. This study illuminates the untapped potential of vehicular solar heat capture, highlighting its feasibility, diverse applications, and significant implications for sustainable energy strategies and community development